Polyphenol-rich extract from blackcurrant pomace attenuates the intestinal tract and serum lipid changes induced by a high-fat diet in rabbits - Jurgoński, Adam (Eur J Nutr, 2014)
PURPOSE: The consumption of a high level of dietary extract from blackcurrant pomace rich in polyphenols was hypothesised to exert beneficial effects on the serum lipid profile, the markers of insulin resistance and the antioxidant status of the host without negative changes in the intestinal tract. METHODS: This hypothesis was tested on 20 male New Zealand white rabbits randomly assigned to four groups of five individuals each. For 4 weeks, the animals were subjected to the following dietary treatments: two control groups were fed a standard or a high-fat diet (7 and 32 % energy from fat, respectively), and two experimental groups were fed a standard or a high-fat diet with the addition of 1.5 % blackcurrant polyphenolic extract. The extract obtained from blackcurrant fruit pomaces was characterised by high concentrations of anthocyanins and flavonols (48.9 and 17.9 %, respectively). RESULTS: The high-fat feeding regimen led to a series of unfavourable changes, such as increased body weight, disturbance of fermentative processes in the hindgut as well the induction of oxidative stress, hyperlipidaemia and insulin resistance. Dietary supplementation with blackcurrant extract decreased the concentration of putrefactive metabolites (ammonia and putrefactive SCFA) and β-glucuronidase activity in the hindgut digesta. Additionally, the extract ameliorated hyperlipidaemia by decreasing triglyceride, total cholesterol, non-HDL cholesterol and free fatty acid concentrations in the serum and increased the antioxidant capacity of the serum. CONCLUSION: This study suggests that a polyphenol-rich extract from blackcurrant pomace ingested at relatively high amounts may be a useful therapeutic option in the reversal of dysfunctions related to obesity and its complications.